Brain temperature during 340-kHz pulsed ultrasound insonation: a safety study for sonothrombolysis - Fatar, Marc; Stroick, Mark Gregor; Griebe, Martin; Alonso, Angelika; Hennerici, Michael G.; Daffertshofer, Michael (Stroke, 2006)
BACKGROUND AND PURPOSE: Because ultrasound is used for improving thrombolysis of cerebral infarction but continuous ultrasound insonation also has significant thermal effects, we evaluated brain temperature increase and tissue destruction during pulsed ultrasound emission. - METHODS: We examined 340-kHz pulsed ultrasound effects in male Wistar rats. Ultrasound was applied transcranially for 30 minutes on different power levels (1 to 7 W/cm2). Temperature was measured at different locations (brain, in the focus of ultrasound beam, inner ear, temporalis muscle, and rectum). The cooling time after 30-minute insonation for every power level was recorded, and animals were examined by postmortem brain histology (TUNEL and hematoxylin/eosin). - RESULTS: Brain temperature increased within 2 to 5 minutes of insonation. Brain temperature increase and cooling time were in proportion to power level, and even with the highest intensity of 7 W/cm2 for 30 minutes, the maximum elevation of mean brain temperature was 0.9 degrees C, with the highest cooling time of 40 minutes. No deleterious side effects of this treatment could be found in histological examination. - CONCLUSIONS: Using a pulsed ultrasound design, only a moderate temperature increase could be observed with no histopathological abnormalities. Deleterious side effects of mid-kilohertz ultrasound (eg, intracerebral hemorrhage) are therefore not a consequence of local brain temperature increase.